A new children's hospital with a larger floor space, single rooms, and V-shaped ward design: A pre–post evaluation of nurse time providing patient care and nurse, patient, and family experiences. Issue 2 (April 2023) - Gill, Fenella J; Nelson, Helen; Bear, Natasha; Tallon, Mary; Pienaar, Catherine; Ferullo, Jade; Baker, Sue
Background: The impact of hospital building design on patients, families and nurses related to nursing care interactions is not well understood. This study reports a pre–post intervention study to understand the effects of the move to a new children's hospital in Perth, Australia, on nurse workflow activities and on patient, family, and nurse experiences. Methods: We used a pre–post explanatory sequential design involving observation of nurse work tasks; measurement of the Practice Environment Scale and Nurse Work Index; weekly surveys of nurse, patient and family experiences; and nurse focus groups and interviews with patients and families. Survey data were analysed using linear regression; qualitative data analysis used a thematic approach. Results: Nurse time spent walking almost doubled ( p < 0.001), from an estimated 10 min at T1 (pre-move) to around 20 min at T4 (12 months post-move), but there was no difference in nurse time providing patient care ( p = 0.114). The Practice Environment Scale and Nurse Work Index showed significantly reduced scores for nursing foundations for quality of care (adjusted mean difference −0.08, p = 0.016) and staffing and resource adequacy (adjusted mean difference −0.19, p < 0.001).This fall was mirrored in nurse experience surveys with a reduction in mean scores from T1 to T3 (3 months post-move) of −0.7 ( p < 0.001) and from T1 to T4 of −0.4 ( p = 0.002). Thematic analysis of qualitative data found that initial challenges appeared to reduce over time. Nurses reported difficulties managing workflow in the new wards and feelings of exhaustion at T3, but this changed to more positive accounts at T4. For patients and families there was a tension between leaving the old and familiar, enjoying the light and space of the new and shared observations that nurses appeared to be busier at T3. At T4, these experiences had changed to 'being a family in hospital' and confidence that a nurse was always close by. Conclusions: Both benefits and challenges of the new hospital design were encountered from the perspective of nurses, patients, and families. Nurses spent double the time walking in the new environment, but time spent providing patient care was unchanged. Over time, the initial practice challenges reduced as nurses adapted to working in the new environment. Trial Registration: ACTRN12618000775213.